2017
DOI: 10.1038/tp.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of striatal dopamine responsiveness by Notch/RBP-J signaling

Abstract: Dopamine signaling is essential for reward learning and fear-related learning, and thought to be involved in neuropsychiatric diseases. However, the molecular mechanisms underlying the regulation of dopamine responsiveness is unclear. Here we show the critical roles of Notch/RBP-J signaling in the regulation of dopamine responsiveness in the striatum. Notch/RBP-J signaling regulates various neural cell fate specification, and neuronal functions in the adult central nervous system. Conditional deletion of RBP-J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…However, Notch/RBP-J signalling plays a key role in the regulation of dopamine responsive as neuron-specific loss of Notch/RBP-J signalling has been shown to cause a deficit in dopamine-dependent instrumental avoidance learning and hyper-responsiveness to apomorphine and SKF38393, a D1 agonist. 75 Brain-derived neurotrophic factor (BDNF) transcriptionally regulates DARPP-32 expression in neurons, as exemplified by delayed and decreased neuronal DARPP-32 expression in BDNF knockout mice, a phenotype that could be rescued ex vivo through the addition of BDNF to cultured neurons derived from BDNF null mice. 76 BDNF and ASCL1 were dysregulated and accompanied by aberrant expression of DARPP-32, one of their common transcriptional targets, in striatal neural stem cells derived from a hypoxanthine-guanine phosphoribosyltransferase (HPRT) knockout mouse model of Lesch-Nyhan Syndrome, a neurodevelopmental disorder caused by mutations in the gene encoding HPRT.…”
Section: Discussionmentioning
confidence: 99%
“…However, Notch/RBP-J signalling plays a key role in the regulation of dopamine responsive as neuron-specific loss of Notch/RBP-J signalling has been shown to cause a deficit in dopamine-dependent instrumental avoidance learning and hyper-responsiveness to apomorphine and SKF38393, a D1 agonist. 75 Brain-derived neurotrophic factor (BDNF) transcriptionally regulates DARPP-32 expression in neurons, as exemplified by delayed and decreased neuronal DARPP-32 expression in BDNF knockout mice, a phenotype that could be rescued ex vivo through the addition of BDNF to cultured neurons derived from BDNF null mice. 76 BDNF and ASCL1 were dysregulated and accompanied by aberrant expression of DARPP-32, one of their common transcriptional targets, in striatal neural stem cells derived from a hypoxanthine-guanine phosphoribosyltransferase (HPRT) knockout mouse model of Lesch-Nyhan Syndrome, a neurodevelopmental disorder caused by mutations in the gene encoding HPRT.…”
Section: Discussionmentioning
confidence: 99%
“…The third transcription factor identified, Rbpj1, is a member of a family of molecules that are an integral part of Notch signaling, which regulates cell differentiation, cell fate, and neural progenitor selfrenewal (Roese-Koerner et al, 2017). Interestingly, Rbpj1 also regulates dopamine responsiveness in the striatum and may be a predictor of vulnerability to psychiatric disease (Toritsuka et al, 2017). Overall, the ontology and binding motif analyses identified established and novel pathways in neurons that are associated with volitional cocaine consumption.…”
Section: Discussionmentioning
confidence: 99%
“…A recent mouse study has intriguingly identified a link between Notch/RBP-J and striatal dopamine function (Toritsuka et al, 2017). Conditional knockout of RBP-J (Su(H) in flies) in neurons decreased striatal dopamine release, increased D1 agonist responsivity, and affected the acquisition and maintenance of conditioned avoidance behavior (Toritsuka et al, 2017). Since D1 and D2 receptor binding and expression were not altered in the absence of RBP-J , the cellular mechanisms of how Notch/RBP-J signaling affects dopaminergic activity still remain unclear.…”
Section: Discussionmentioning
confidence: 99%